2013
DOI: 10.1007/s10152-013-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive patterns of blacktail comber (Serranus atricauda, Serranidae) from south-west Portugal seamounts

Abstract: The knowledge of the reproductive strategy is essential for the comprehensive understanding of the population dynamics of any fish species. This study intends to define the spawning season, verify the type of fecundity regulation and estimate relative annual fecundity for Serranus atricauda inhabiting the south-west of Portugal seamounts (Gorringe, Ampère and Lion). Monthly samples, between September 2010 and December 2011, were obtained from commercial vessels. This species is synchronously hermaphroditic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(30 reference statements)
5
2
0
Order By: Relevance
“…However, the values of RBF found in this study were close to those reported by Alós, Alonso‐Fernández, Catalán, Palmer, and Lowerre‐Brabieri () and Neves et al. () for the simultaneous hermaphrodites S. scriba (mean of 83 hydrated oocytes/g) and S. atricauda (mean of 22 hydrated oocytes/g), respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the values of RBF found in this study were close to those reported by Alós, Alonso‐Fernández, Catalán, Palmer, and Lowerre‐Brabieri () and Neves et al. () for the simultaneous hermaphrodites S. scriba (mean of 83 hydrated oocytes/g) and S. atricauda (mean of 22 hydrated oocytes/g), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported for other hermaphrodite species such as D. formosum by Obando and León (), Serranus scriba by Tuset et al. () and S. atricauda by Neves, Sequeira, Paiva, Vieira, and Gordo ().…”
Section: Discussionsupporting
confidence: 89%
“…This relative low production might be related to the spawning frequency of this species that must be high to compensate the low number of hydrated oocytes produced. However, the values of RBF found in this study were close to those reported by Alós et al (2013) and Neves et al (2014) Fecundity is also affected by the fish size, weight and condition, being the key parameters to assess fecundity at the population level (KJESBU et al, 1991;. Thus, the RBF was negatively affected by all factors measured, revealing that the smaller specimens with a better condition produce more hydrated oocytes per gram of body.…”
Section: Reproductive Traits Of the Simultaneous Hermaphrodite Dipletsupporting
confidence: 45%
“…This type of ovarian organisation is typical of multiple spawning species with a very protracted spawning Obando and León (1989), Serranus scriba by Tuset et al (2005) and S. atricauda by Neves et al (2014). Multiple spawning fishes with indeterminate fecundity usually produce large batches of hydrated oocytes (GANIAS et al, 2004;GRANDE et al, 2014;GARCÍA-SEOANE et al, 2014).…”
Section: Reproductive Traits Of the Simultaneous Hermaphrodite Dipletmentioning
confidence: 99%
See 1 more Smart Citation